2007
DOI: 10.2139/ssrn.991886
|View full text |Cite
|
Sign up to set email alerts
|

Negligence, Ignorance and the Demand for Liability Insurance

Abstract: This paper considers whether lack of information regarding risk exposures can lead to a demand for negligence liability insurance. We find that, under the uniform negligence rule, such as the "reasonable person" standard used to determine negligence in the U.S. and other countries, the value of information is positive and any demand for liability insurance must come from informed individuals. The necessary and sufficient condition is that good risks find it less costly to be negligent and purchase insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…24 According to a 1996 Conning & Co. insurance fraud study, ''Insurance Fraud: The Quiet Catastrophe'', it is estimated that P/C insurers detect about 20 per cent of their fraud, while life/disability insurers find about 10 per cent and health care insurers a mere 1 per cent. A June 2000 study by the Insurance Research Council in the U.S. revealed that 35 per cent of Americans surveyed said that it is all right to exaggerate 22 Bajtelsmit and Thistle (2009). 23 Crocker and Doherty (2000).…”
Section: Asymmetric Information and Insurance Fraudmentioning
confidence: 99%
“…24 According to a 1996 Conning & Co. insurance fraud study, ''Insurance Fraud: The Quiet Catastrophe'', it is estimated that P/C insurers detect about 20 per cent of their fraud, while life/disability insurers find about 10 per cent and health care insurers a mere 1 per cent. A June 2000 study by the Insurance Research Council in the U.S. revealed that 35 per cent of Americans surveyed said that it is all right to exaggerate 22 Bajtelsmit and Thistle (2009). 23 Crocker and Doherty (2000).…”
Section: Asymmetric Information and Insurance Fraudmentioning
confidence: 99%